Effect of anisotropic thermo-elastic properties of woven-fabric laminates on diagonal warpage of thin package substrates. (15th September 2017) - Lee, Tae-Ik; Kim, Cheolgyu; Pyo, Jae-Bum; Kim, Min Sung; Kim, Taek-Soo
Abstract: Warpage of thin package substrates and their in-plane orientation at room temperature were studied, focusing on the thermo-elastic properties of woven-fabric (WF)/epoxy laminates. It was recently observed that most of the severe warpage of thin package substrates fabricated from WF laminates was diagonal, which lowers significantly the yields of various processes. The final strip warpage primarily originates from residual stress of the first base substrate, a copper clad laminate (CCL). Therefore, we investigated the built-in residual stress, which develops during the thermo-compression bonding of the CCL. For this study, CCL specimens with 100–150 μm thick WF laminates were prepared in order to understand the warpage mechanism. Flexural moduli and coefficients of thermal expansion (CTE) of the composite substrates were accurately measured in four orientations (0, 45, 90, 135)° to correlate with the warpage orientation using a three-point bending test and digital image correlation method, respectively. The mechanism that determines warpage orientation was verified using finite element simulation, indicating the importance of considering both orthotropic elastic modulus and anisotropic CTE with a non-zero shear CTE of the thin WF laminate in warpage analysis.